231k views
5 votes
Fill in the table using this function rule.
y = -4.x-3

Fill in the table using this function rule. y = -4.x-3-example-1

1 Answer

7 votes

Answer:

When x = -2, y = 5

When x = 0, y = -3

When x = 2, y = -11

When x = 4, y = -19

Explanation:

Using these values you can just substitute them and then find the y value using the function rule y = -4x-3:

x is -2:


y = (-4)(-2)-3


y = 5

x is 0:


y = (-4)(0)-3


y=-3

x is 2:


y = (-4)(2) - 3


y = -11

x is 4:


y = (-4)(4)-3


y=-19

User Kousik
by
4.7k points